2009
DOI: 10.1002/lt.21777
|View full text |Cite
|
Sign up to set email alerts
|

Serial measurement of Doppler hepatic hemodynamic parameters for the diagnosis of acute rejection after live donor liver transplantation

Abstract: To elucidate the role of Doppler hepatic hemodynamic parameters as surrogate markers of acute rejection (AR) after live donor liver transplantation (LDLT), serial Doppler measurements were prospectively performed during the first 2 weeks after LDLT to compare the longitudinal hepatic hemodynamic changes between patients with histologically proven AR and patients without histologically proven AR. Forty-six patients that had undergone adult-to-adult LDLT using a right lobe graft were enrolled in this study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Not surprisingly, bile duct dilatation and cholestasis were correlated (RRR = 7.7); however, because of the large CI (2–29), the result is not precise. Some studies have demonstrated relations between US parameters, mainly hepatic vein waveforms and portal blood velocity, and acute rejection typically within 2 weeks after transplantation (11,13,15,16); however, the contrary has also been reported (14). Study methods and definitions, cohorts, and timing of biopsy posttransplantation likely account for variability in these results and those of our study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Not surprisingly, bile duct dilatation and cholestasis were correlated (RRR = 7.7); however, because of the large CI (2–29), the result is not precise. Some studies have demonstrated relations between US parameters, mainly hepatic vein waveforms and portal blood velocity, and acute rejection typically within 2 weeks after transplantation (11,13,15,16); however, the contrary has also been reported (14). Study methods and definitions, cohorts, and timing of biopsy posttransplantation likely account for variability in these results and those of our study.…”
Section: Discussionmentioning
confidence: 55%
“…What is understood in adult cohorts is that standard LFTs do not correlate well in many cases of grading the severity of liver graft dysfunction (6)(7)(8). Similarly, Doppler US variables have been investigated as predictors of posttransplantation liver rejection, but these studies have used mostly or exclusively adult cohorts, focused on the time period within 2 weeks or shortly after transplantation, and/or preceded an international consensus of defining rejection (9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…However, the relationship between bilirubin levels and In Doppler ultrasonographic measurements, MHVV was associated with TCMR and histological central venulitis. Previous studies have shown that PHVV at postoperative day 5 and hepatic vein wave form were associated with acute TCMR, 21,[32][33][34] and the relationship between MHVV and acute TCME has not been studied. Globular swelling severity and luminal narrowing of the hepatic vein on computed tomography scan were found to be associated with increases in the risk of acute TCMR because histopathological inflammation alters hepatic compliance and leads to graft swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Имеются трудности верификации этого процесса и при использовании визуализаионных, в том числе и ультразвуковых методов диагностики [31]. Исследователями не найдено достоверных ДГ признаков его подтверждения [29,40]. В то же время, Martino M.D.…”
Section: несосудистые осложненияunclassified